2012
DOI: 10.1002/app.37802
|View full text |Cite
|
Sign up to set email alerts
|

Moderately high refractive index, low optical dispersion polymers with pendant diamondoids

Abstract: Soluble, colorless polymers containing pendant diamondoid moieties (adamantane and diamantane) were synthesized and characterized. The materials exhibited an unusual combination of moderately high refractive index with low optical dispersion. These properties may make the polymers valuable as specialty optical plastics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 42 publications
0
35
1
Order By: Relevance
“…The refractive indices of samples 4 and 7 are 1.543 and 1.522, respectively. PAdMA (sample 7) obtained in this study shows a slightly higher refractive index than the previously reported value of 1.511 …”
Section: Resultscontrasting
confidence: 74%
See 2 more Smart Citations
“…The refractive indices of samples 4 and 7 are 1.543 and 1.522, respectively. PAdMA (sample 7) obtained in this study shows a slightly higher refractive index than the previously reported value of 1.511 …”
Section: Resultscontrasting
confidence: 74%
“…T g varies in the range 200–244 °C depending on the molecular weight ( M n = 0.46 × 10 4 –3.21 × 10 4 g mol −1 ). Recently, Robello also prepared PAdMA by ATRP and reported that T g was 240 °C when M n was 0.63 × 10 4 g mol −1 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, their dielectric constant can be tailored by varying the overall length of the arms. 116 The unusual combination of moderately high refractive index with low optical dispersion properties lead to the formation of unique optical plastics. Polymers with diamondoids as pendants offer high thermal stability, excellent transparency, solubility in organic solvents, and etching resistance, as well as good processability.…”
Section: Diamondoids In Crosslinking Networkmentioning
confidence: 99%
“…In bridged and non-polar polycyclic hydrocarbon structures, rigidity and three-dimensional size contribute to a high free volume, low moisture absorption and absence of π-electrons to lower the dielectric constant and increase optical transparency in the visible region [5][6][7][8][9][10][11][12][13]. Consequently, we hypothesized that incorporation of bulky, rigid tricycloalkyl substituents into PMMA would improve the thermal and mechanical properties of the polymer and maintain good optical and dielectric properties to result in high-performance, high-value materials for use in microelectronic and optoelectronic applications.…”
Section: Introductionmentioning
confidence: 99%